2009
DOI: 10.1080/07347320802587005
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and Its Relationship to Serenity and Anger/Impulsivity in an Alcohol and Other Drug-Dependent Population: Implications for Treatment

Abstract: This study assessed the relationships between self-esteem, serenity, and anger/impulsivity in a chronic alcohol and other drug (AOD) dependent population. Three hundred participants completed questionnaires addressed to substance abuse, self-esteem, serenity, anger/impulsivity, and other variables. Pearson rs of between .55 and .61 were found between self-esteem and serenity, anxiety, and anger/impulsivity. Regression analyses indicated that the self-esteem of chronic AOD-dependent individuals was best This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…An examination of the correlates of anger among substance users is critical since anger has been shown to negatively impact treatment for SUD (Litt et al, 2000;Pekala, Kumar, Maurer, Elliott-Carter, & Moon, 2009;Witkiewitz & Villarroel, 2009). Furthermore, elevated anger among individuals with SUD has also been shown to be associated with the perpetration of violence (Giancola, 2002b;Giancola, Saucier, & Gussler-Burkhardt, 2003;Parrott & Zeichner, 2002).…”
Section: Anger Among Individuals With Sudmentioning
confidence: 99%
“…An examination of the correlates of anger among substance users is critical since anger has been shown to negatively impact treatment for SUD (Litt et al, 2000;Pekala, Kumar, Maurer, Elliott-Carter, & Moon, 2009;Witkiewitz & Villarroel, 2009). Furthermore, elevated anger among individuals with SUD has also been shown to be associated with the perpetration of violence (Giancola, 2002b;Giancola, Saucier, & Gussler-Burkhardt, 2003;Parrott & Zeichner, 2002).…”
Section: Anger Among Individuals With Sudmentioning
confidence: 99%
“…Recently, study samples have expanded from those composed of the general population to those including special groups, such as people with schizophrenia spectrum disorders (Lysaker, Davis, & Tsai, 2009), sexually abused adolescents (Asgeirsdottir, Gudjonsson, Sigurdsson, & Sigfusdottir, 2010), and persons dependent on alcohol and other substances (Pekala, Kumar, Maurer, Elliott-Carter, & Moon, 2009). Studies with such samples have shown that high self-esteem can significantly predict low anger.…”
Section: Introductionmentioning
confidence: 99%
“…Both significantly increase the risk of relapse (Ungless et al, 2010). Low self-esteem or serenity, high impulsivity, and anger also increase relapse risk and are impacted by interpersonal relations (Pekala et al, 2009). …”
Section: Introductionmentioning
confidence: 99%